Accessing Impacts of Banks and Financial Institutions Act in the Development of Financial Sector - Pokharel, Ram Sharan (Kathmandu School of Law Review, 2018)
The main objective behind the establishment of Nepal Rastra Bank in 1956, as per the then Nepal Rastra Bank Act, 2012 B.S. (Now Nepal Rastra Bank Act, 1955), was to maintain macro-economic stability, by adopting sound and effective monetary, foreign exchange and financial sector policies. Institutional Development and Legal Development are the main underlying components to achieve the objectives of macroeconomic stability along with the development of Regulatory Authority and market mechanism subject to Institutional Development. Ministry of Finance, Nepal Rastra Bank, Securities Board of Nepal, Insurance Board, etc. form Regulatory Authorities whereas banks and financial institutions, securities brokers, merchant bankers, insurance companies form the Market Mechanism. This article, does not give much attention to institutional development, aims mainly to emphasize on the impacts of legal input in the development of financial sectors of Nepal, especially, the promotion of Banks and Financial Institutions and its impacts in the financial sector and the impacts of Banks and Financial Institutions Act (BAFIA) in the development of Banks and Financial Institutions, respectively. The history of modern banking in Nepal is yet to complete 100 years as it is evident from the establishment of Nepal Bank Limited in 1937. Prior to the establishment of Nepal Bank Limited, limited amount of bank transactions used to be done by Tejarath Adda which was established in 1880. Tejarath Adda did not collect deposit but it used to disburse loan. However, it did not provide loan to general people, rather it used to provide loan to government employees and land-lords only. Nevertheless, the government had provided loan to general people through Tejarath Adda to build house after the great earthquake of 1934. The modern banking history of Nepal commenced after the establishment of Nepal Bank Limited in 1937. Subsequently, Nepal Industrial Development Corporation, Agricultural Development Bank, Rastriya Bannijjya Bank, Nepal Arab Bank Limited, Nepal Indosuez Bank Limited (which later became Nepal Investment Bank Limited), Nepal Grindlays Bank Limited (which later became Standard Chartered Bank Nepal Limited), Himalayan Bank Limited, and the youngest bank Mega Bank Limited have been established in series. Now, Nepal Rastra Bank has stopped licensing process of Banks and Financial Institutions except Infrastructure Bank.